PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP RESPON INVESTOR DALAM SEKTOR KEUANGAN - Dianita Stefany (Business Accounting Review, 2015)
There were many researches about the effect of Corporate Social Responsibility on investor response, but the results were still inconsistent. This research aimed to examine the effect of Corporate Social Responsibility (CSR) on investor response in companies in the financial sector. In this research, CSR was measured by CSR index, based on criteria established by the Global Reporting Initiative (GRI), while investor response was measured by the Cumulative Abnormal Return (CAR). This research used four control variables, were consisted of return-on-assets (ROA), firm size, debt-to-equity ratio (DER), and market share. The hypothesis in this research were tested by using multiple regression analysis. The samples used in this research are 310 firm years in the financial sector that were listed in Indonesia Stock Exchange in the period of 2008-2012.            The result of this research concluded that CSR had significant negative effect on investor response. As control variables, ROA and firm size had significant positive effect, DER had significant negative effect, while market share had no significant effect on the investor response.